Kemampuan Siswa Kelas VIII SMP Negeri 3 Ingin Jaya Menyimpulkan Isi Berita Yang Didengar - Rahmad Dana Achar Harahap; Razali Razali; Sa’adiah Sa’adiah (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
The title of this study was The Student Ability of VIII Class SMP Negeri 3 Ingin Jaya Student in Concluding The Audio News Report. The aims of this study was to describe the student ability in concluding the audio news report on audio media. The qualitative approach with descriptive methods had been used in this study. Sampling method used in this study was a random sampling method. A total of 32 student of VIII-1 class participated as part of sample that included 8 men and 24 women. The data colection was done by  using test techniques. The student ability to identify news elements was assessed based on the student ability to identify what, who, where, when, why, and how elements. The student ability to conclude the news was assessed based on the news element completeness, news conclusions suitability, and orthography accuracy. The resul showed that  the average score of student ability to identify news elements (5W+1H elements) was 95,06, while the average score of ability to conclude the news was 80,05. Based on the study result, it concluded that the student ability in identifying the audio news report elements was very good, while the ability in concluding the audio news report was good.